Development and Modification of a Single Overhead Camshaft 4-Valve 4-Stroke 135 cc Formula Varsity Race Car Engine - ABDULLAH, Mohd Azman; Tamaldin, Noreffendy; Rusnandi, Herdy; Manoharan, Tayalan; Samsir, Muhammad Afiq (IOP Publishing, 2013)
The engine that was chosen to be developed and modified is Yamaha LC 135 Single Overhead Camshaft (SOHC) 4-valve 4-stroke 135cc liquid-cooled engine. The engine selection is based on the specification, rule and regulation in UTeM Formula Varsity 2012 (FV 2012). The engine performance is determined by engine operating characteristics. The engine air flow affects the filtration, intake and exhaust systems. The heat from the engine rejected to the surrounding through the active cooling system which has radiator and fan. The selection of the engine is based on weighted decision matrix which consists of reliability, operating and maintenance cost, fuel consumption and weight. The score of the matrix is formulated based on relative weighted factor among the selections. It been compared between Yamaha LC 135 Single Overhead Camshaft (SOHC) 4-valve 4-stroke 135cc liquid-cooled engine, Honda Wave 125 X Air Cooled, 4 Cycle Engine Overhead Camshaft (OHC) and Suzuki Shogun RR 4 stroke air cooled Single Overhead Camshaft (SOHC). The modification is applied to the engine through the simulation and tuning of Capacitor Discharge Ignition (CDI).